The dormancy of parliaments: the invisible cause of judiciary empowerment in central and eastern Europe - Parau, C (Routledge, 2013)
The exceptional empowerment of the judiciary lately transpiring across post-communist Central and Eastern Europe (CEE) exhibits an institutional design uniformity that reflects a common origin in a networked, transnational legal professional epistemic community-cum-community of interest. Their template's success, however, heretofore inadequately explained, is traceable to an equally important but less observable causal factor: the dormancy in originating norms; in overseeing designers; and in vetoing one's own disempowerment.